Spotlight on Data : The Ethics of Analytics with Bill Franks - Franks, Bill (O'Reilly Media, Inc., 2020)
The more data we collect, the more concerned we are (or should be) about what data is appropriate and how-or if-it should be analyzed. There are many ethical, privacy, and legal issues to consider, and no clear standards exist as to what's fair and what's foul. This means that in order to implement the right policies, organizations must devise their own principles and tolerance for risk. In this Spotlight on Data , learn about the range of ethical, privacy, and legal issues that surround analytics today. Bill Franks will frame the big questions every successful business must consider while outlining some of the trade-offs and ambiguities they need to address to answer them. Recorded on November 13, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Data , you'll learn about, discuss, and debate the tools, techniques, questions, and quandaries in the world of data. You'll discover how successful companies leverage data effectively and how you can follow their lead to transform your organization and prepare for the Next Economy.